Kewewenangan Pendamping Desa Dalam Pembangunan Dan Kemandirian Desa - Dedi Sufriadi (Jayapangus Press, 2019)
The existence of village facilitators must move quickly in developing strategies in resolving poverty and reducing social inequality, of course the target is physical development, and village infrastructure with the aim of opening as wide as possible to developing villages. The existence of village facilitators was formed to organize government affairs and the interests of the local village community in accordance with the mandate of the Republic of Indonesia Law Number 6 of 2014 concerning Villages. The formation of village facilitators was the result of reforms as an effort to realize democracy at the village level. Village facilitators have a very important influence in the village government, namely digging, accommodating and channeling community aspirations in the development of rural areas in a participatory manner as well as increasing capacity for village governments, village social institutions in terms of development and empowerment of rural communities so that the community hopes for the program programs that will be implemented by the government, especially for community welfare and own village development. Implementation of companion authority in the framework of development and independence in the Lingom Village of Indrapuri Sub-District, Aceh Besar Regency has been quite helpful in the welfare of rural communities whose majority are farmers. However, this has not yet been achieved because there are several obstacles in carrying out their authority as village facilitators. It is best for village facilitators and village governments to jointly increase village community participation to improve performance optimization, and to synergize in carrying out their duties and functions to realize smoothness in terms of development in the village.